1992
DOI: 10.1002/ijc.2910510109
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor and immunomodulatory activity of intraperitoneal IFN‐γ in ovarian carcinoma patients with minimal residual tumor after chemotherapy

Abstract: Eight patients with epithelial ovarian carcinoma persisting after chemotherapy, selected for having a residual tumor no larger than 1 cm in diameter, were treated intra-peritoneally (i.p.) with recombinant interferon-gamma twice weekly for 3 months. Toxicity consisted of fever and malaise in all patients and a transient rise in hepatic enzyme levels in 3 patients. The cytotoxic function of peripheral blood and peritoneal tumor-associated lymphocytes (TAL) and macrophages (TAM), was studied using cell lines as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…40 Previous reports indicated that IFNc sensitizes ovarian carcinoma cells to the cytotoxic effect of TNFa and cisplatin 41 and has antitumor effects in ovarian carcinoma patients by intraperitoneal administration. 42,43 Altogether these previous data suggest that mat-IL-18-driven IFNc production by lymphoid cells present at the tumor site would inhibit ovarian tumor growth. In this report, we show that patients with high levels of IL-18 in the serum or in the ascites display low levels of IFNc, further suggesting that the IL-18 accumulating in patient's fluids is biologically inactive and unable to activate an immune response.…”
Section: Tumor Immunologymentioning
confidence: 78%
“…40 Previous reports indicated that IFNc sensitizes ovarian carcinoma cells to the cytotoxic effect of TNFa and cisplatin 41 and has antitumor effects in ovarian carcinoma patients by intraperitoneal administration. 42,43 Altogether these previous data suggest that mat-IL-18-driven IFNc production by lymphoid cells present at the tumor site would inhibit ovarian tumor growth. In this report, we show that patients with high levels of IL-18 in the serum or in the ascites display low levels of IFNc, further suggesting that the IL-18 accumulating in patient's fluids is biologically inactive and unable to activate an immune response.…”
Section: Tumor Immunologymentioning
confidence: 78%
“…It has been reported that recruitment of TAMs is due to cancer-cell-mediated upregulation of host stromal cell production of colony-stimulating factor-1 [19]. TAMs stimulate tumor growth, produce angiogenic factors [20] and facilitate vascular invasion of tumor cells [21,22]. It has also been reported that the invasiveness of tumors co-cultured with macrophages is enhanced by tumor necrosis factor-α and MMPs released from macrophages [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…IFNg has been shown to re-educate TAM [64] and there is proof of principle evidence for antitumor activity of this molecule in minimal residual disease in humans [65][66][67]. Given the protumor function of TAM in many cancer, strategies have been directed at blocking recruitment (see above) targeting chemokines or CSF-1 or inhibiting TAM directly [68,69 ,70].…”
Section: Tipping the Balancementioning
confidence: 99%